ТРИ ВАРИЈАНТЕ ЈЕДНЕ СТАРЕ ПРИЧЕ. О СНУ И ЈАВИ ЦАРА АСЕ (Prilozi za književnost, jezik, istoriju i folklor, 2023)
The paper deals with three similar tales – Of too much Pride, the story about Emperor Jovinian from Gesta Romanorum (Oesterley, 1872), The Story of Tsar Aggey and how he Suffered for Pride (Afanasev, Narodnye russkie legendy, 1859), and Asa The Emperor (Daničić, Three Old Tales, 1872). The story about Emperor Asa, the third king of the Kingdom of Judah (2 Chronicles 14–16), is preserved in only one Serbian-Slavonic manuscript from the end of the 16th century (now in The Patriarchal Library of the Serbian Orthodox Church, No. 167). Its main motif is the atonement of sin (Emperor’s deletion of three verses written by a woman from the holy books). In three days of punishment he will find himself in the alternative reality (of the dream), on a rubbish dump, dressed in rags, uncertain who he actually is. At the end of his “waking dream” enlightened Asa will solemnize the Providence of God. The aim of this research is to establish some important literary aspects of shaping Asa’s character.